Bioelectricity generation from pig farm wastewater in microbial fuel cell using carbon brush as electrode. (28th September 2016) - Ma, Jun; Ni, Hongjun; Su, Dongyun; Meng, Xiangkang
Abstract: As microbial fuel cell (MFC) technology is getting nearer to practical applications, the microorganisms can convert chemical energy from a wide range of organic substances into electric current directly. In this paper, the MFC with a spherical configuration as cathode compartment was constructed. The MFC with a brush-shaped anode, platinum/carbon cathode, pre-treated Nafion 117 were constructed using pig farm wastewater as substrate. The biofilm analysis was used by bacterial community structure and diversity by denaturing gradient gel electrophoresis (DGGE). A benthic strain of proteobacteria was isolated and identified, wastewater was treated with proteobacteria to decrease the chemical oxygen demand, phosphorus, nitrogen and to produce electricity, which had an excellent electrogenic qualities. Highlights: The MFC constructed with a spherical configuration as a cathode compartment has a better anti-leakage performance. Carbon brush anodes achieve a good dispersion of the graphite filaments and contain an efficient current collector. A benthic strain of proteobacteria was isolated and identified.